Atrial Fibrillation Burden in Young Patients With Congenital Heart Disease. Issue 9 (27th February 2018) - Mandalenakis, Zacharias; Rosengren, Annika; Lappas, Georg; Eriksson, Peter; Gilljam, Thomas; Hansson, Per-Olof; Skoglund, Kristofer; Fedchenko, Maria; Dellborg, Mikael
Abstract : Background: Patients with congenital heart disease (CHD) are assumed to be vulnerable to atrial fibrillation (AF) as a result of residual shunts, anomalous vessel anatomy, progressive valvulopathy, hypertension, and atrial scars from previous heart surgery. However, the risk of developing AF and the complications associated with AF in children and young adults with CHD have not been compared with those in control subjects. Methods: Data from the Swedish Patient and Cause of Death registers were used to identify all patients with a diagnosis of CHD who were born from 1970 to 1993. Each patient with CHD was matched by birth year, sex, and county with 10 control subjects from the Total Population Register in Sweden. Follow-up data were collected until 2011. Results: Among 21 982 patients (51.6% men) with CHD and 219 816 matched control subjects, 654 and 328 developed AF, respectively. The mean follow-up was 27 years. The risk of developing AF was 21.99 times higher (95% confidence interval, 19.26–25.12) in patients with CHD than control subjects. According to a hierarchical CHD classification, patients with conotruncal defects had the highest risk (hazard ratio, 84.27; 95% confidence interval, 56.86–124.89). At the age of 42 years, 8.3% of all patients with CHD had a recorded diagnosis of AF. Heart failure was the quantitatively most important complication in patients with CHD and AF, with a 10.7% (70 of 654) recorded diagnosis of heart failure. Conclusions: The risk of AF in children and young adults with CHD was 22 times higher than that in matched control subjects. Up to the age of 42 years, 1 of 12 patients with CHD had developed AF, and 1 of 10 patients with CHD with AF had developed heart failure. The patient groups with the most complex congenital defects carried the greatest risk of AF and could be considered for targeted monitoring. Abstract : Supplemental Digital Content is available in the text.